2019
DOI: 10.1371/journal.pone.0222382
|View full text |Cite
|
Sign up to set email alerts
|

Levels of serum eosinophil cationic protein are associated with hookworm infection and intensity in endemic communities in Ghana

Abstract: BackgroundThe eosinophil cationic protein (ECP) is a cytotoxic protein mainly secreted by eosinophils granulocytes and plays a role in host defense against parasitic infections. Infection with Necator americanus (hookworm) is traditionally diagnosed by the Kato-Katz method which is inherently tedious, subjective and known to underestimate infection intensity. This study aimed to assess levels of serum ECP in relation to hookworm infection intensity.MethodsStool samples from 984 (aged 4 to 80 years) participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 20 publications
3
16
2
Order By: Relevance
“…and hookworm co-infection in Africa (34/37, 91.9%) 8 – 13 , 20 , 24 50 while the remaining studies were from Asia (1 Thai-Burmese border, 1 Indonesia) 51 , 52 or South America (Brazil) 53 . Most of the included studies conducted in Africa were in Nigeria (8/34, 23.5%) 11 , 24 , 28 , 32 , 33 , 45 , 46 , 50 , followed by Ethiopia (6/34, 17.6%) 8 , 9 , 12 , 13 , 31 , 42 , Tanzania (4/34, 11.8%) 38 40 , 49 , Uganda (4/34, 11.8%) 34 , 36 , 44 , 47 , Coˆted’Ivoire (3/34, 8.8%) 10 , 41 , 48 , Ghana (3/34, 8.8%) 26 , 27 , 35 , Kenya (2/34, 5.88%) 30 , 37 , Gabon (2/34, 5.88%) 20 , 25 and Cameroon. One study covered three countries, including Kenya, Ethiopia and Uganda 29 .…”
Section: Resultsmentioning
confidence: 99%
“…and hookworm co-infection in Africa (34/37, 91.9%) 8 – 13 , 20 , 24 50 while the remaining studies were from Asia (1 Thai-Burmese border, 1 Indonesia) 51 , 52 or South America (Brazil) 53 . Most of the included studies conducted in Africa were in Nigeria (8/34, 23.5%) 11 , 24 , 28 , 32 , 33 , 45 , 46 , 50 , followed by Ethiopia (6/34, 17.6%) 8 , 9 , 12 , 13 , 31 , 42 , Tanzania (4/34, 11.8%) 38 40 , 49 , Uganda (4/34, 11.8%) 34 , 36 , 44 , 47 , Coˆted’Ivoire (3/34, 8.8%) 10 , 41 , 48 , Ghana (3/34, 8.8%) 26 , 27 , 35 , Kenya (2/34, 5.88%) 30 , 37 , Gabon (2/34, 5.88%) 20 , 25 and Cameroon. One study covered three countries, including Kenya, Ethiopia and Uganda 29 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 1068 potential study participants aged 4–88 years were randomly identified from a population census data base and recruited into the study. Study subjects ( n = 984) who appeared healthy and were without fever were consented individually prior to providing stool and blood samples [ 16 , 17 ]. Briefly, trained field workers administered a demographic and health questionnaire, and distributed labelled stool-collection containers to the participants.…”
Section: Methodsmentioning
confidence: 99%
“…Trichuris trichiura infections in malaria patients was associated with reduced antibody levels against P. falciparum antigens [ 3 ]. Similarly, Courtin et al, [ 17 ] found Schistosoma haematobium infection to be associated with reduction in IgG levels against P. falciparum antigens MSP-1 and GLURP. Gabonese children infected with Ascaris lumbricoides had a significantly higher P. falciparum anti-gametocyte antibody levels compared to non-infected children [ 4 ].…”
Section: Introductionmentioning
confidence: 95%
“…Eosinophils level was slightly increased in the HW infected group. This may be related to the low intensity of infection [ 36 , 37 ] and the chronicity of infection. Indeed, it has been shown that the levels of eosinophils spontaneously decrease after migration of the larval form [ 38 ].…”
Section: Resultsmentioning
confidence: 99%